LNG-IUS versus GnRH agonist for management of Heavy menstrual bleeding –An alternative Management - Binod Kumar Mahaseth; Mukesh Kumar Shrewastwa (Janaki Medical College Journal of Medical Science, 2025)
Background & Objectives: Heavy menstrual bleeding (HMB) is a prevalent condition affecting a significant proportion of women, particularly during the perimenopausal phase. Traditional management often leads to surgical interventions such as hysterectomy. This study examines the efficacy and safety of the levonorgestrel-releasing intrauterine system (LNG-IUS) compared to GnRH agonists for managing HMB. Materials and Methods: A comparative descriptive study was conducted at Nepalgunj Medical College Teaching Hospital from October 2021 to September 2022. The participants included 37 women in the LNG-IUS group and 30 in the GnRH agonist group, following ethical approval and informed consent. Participants were randomized and evaluated for changes in menstrual blood loss using the Pictorial Blood Loss Assessment Chart (PBAC), hemoglobin (Hb) levels, and hematocrit (Hct) over a 6-month period. Results: At 3 months, the GnRH agonist group demonstrated a significant reduction in menstrual blood loss compared to the LNG-IUS group; however, by 6 months, both groups had achieved similar improvements in menstrual bleeding. The LNG-IUS group showed significant long-term benefits in anemia correction, with higher Hb and Hct levels at the 6-month follow-up compared to the GnRH agonist group. The LNG-IUS also exhibited better retention rates, indicating higher patient acceptability and fewer side effects. Conclusion: The results suggest that while GnRH agonists are effective for short-term symptom relief, LNG-IUS offers sustained improvement in bleeding control and anemia management. The study underscores the importance of personalized treatment options tailored to individual patient needs, factoring in the urgency of symptom relief and long-term health outcomes. Further research is warranted to enhance understanding and address the long-term implications of these treatment modalities in managing HMB.